PENGUATAN KESENIAN LOKAL MELALUI SANGGAR TARI TOR-TOR ELAK-ELAK DI KABUPATEN SIMALUNGUN SUMATERA UTARA DI MASA PANDEMI - Agustono, Budi; Pujiono, Mhd.; Dewi, Heristina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The COVID-19 pandemic has changed many aspects of people's lives. In the field of culture, most of the younger generation ignores the nation's culture, such as traditional dances, and prefers modern dances due to globalization and growing social media. This makes the strategy of strengthening the traditional art group/studio (sanggar) important as a forum for developing creativity in traditional culture in Indonesia, especially North Sumatra. Therefore, in this community service activity, efforts have been made to strengthen sanggar to strengthen the local culture of North Sumatra. This activity was in the form of a Focus Group Discussion (FGD) and dance training for 30 youth members of the sanggar Tortor Elak-Elak in Simalungun Regency, which was carried out for three months. In addition to providing training, the community service team has facilitated supporting equipment in traditional dance performances for sanggar members in the form of clothing, accessories, and other training media. The lecture, Q&A, demonstration, and drill method approaches are used in its implementation. This Community Service has produced outcomes in the form of services to raise public awareness of the local dance culture of North Sumatra with training assistance to increase creativity, innovation, and the ability of sanggar members in the field of culture, a namely traditional dance.